2013
DOI: 10.2147/ca.s41193
|View full text |Cite
|
Sign up to set email alerts
|

Waiting lists in coronary artery bypass graft patients and role of coronary angiography: the Apulian experience

Abstract: Purpose: To evaluate waiting lists during the coronary artery bypass graft (CABG) diagnostictherapeutic pathway of patients, in order to detect the actual waiting time between diagnostic evaluation and surgery, and to explore if coronary angiography provides an option as a starting point of waiting lists for CABG patients. Methods: We analyzed 496 hospital discharge cards (year 2009) from main cardiac surgery units in Apulia, Italy. Exclusion criteria were emergency patients coming from regions other than Apul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Therefore, we need to deal with the last mechanism of ED overcrowding, the “output”, which addresses the capability of a hospital to make available beds in order to discharge patients thus decongesting the emergency room. It is also true that the flows from the ED to the Hospital Departments, are likely to prolong the waiting lists for elective hospitalization [2225]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we need to deal with the last mechanism of ED overcrowding, the “output”, which addresses the capability of a hospital to make available beds in order to discharge patients thus decongesting the emergency room. It is also true that the flows from the ED to the Hospital Departments, are likely to prolong the waiting lists for elective hospitalization [2225]. …”
Section: Discussionmentioning
confidence: 99%
“…It included explaining to the patient the purpose and the course of the surgery, the need and the time of hospitalization, and the necessity for convalescence. Before these patients underwent cardiac surgery, they had undergone coronary angiography and been put on a waiting list, in a manner similar to that described by Ciccone et al 22 The waiting time before surgery can be used for appropriate education (with elements of psychiatry), preparing the patient for surgery in accordance with the model proposed by Ciccone et al, 23 and emphasizing the role of the nurse in improving QoL for patients with heart failure. McHugh et al 21 reported that training not only improved well-being and mood, but also resulted in a quantitative and qualitative reduction of CHD risk factors, such as smoking, body mass index, cholesterol concentrations, physical activity, and arterial blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…During the follow-up, cardiologists and care managers should be in charge of the patient health and self-management. The proper partnership between the care manager and the patient may improve the long-term prognosis [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%